The correct answer is (b) \(\frac{∂^2 ε_x}{∂y^2} +\frac{∂^2 ε_y}{∂x^2} = \frac{∂^2 Γ_{xy}}{∂x∂y}\)
The explanation is: The strain equations in terms of displacements is given by,
\(ε_X=\frac{∂u}{∂x} —————-(1)\)
\(ε_Y=\frac{∂v}{∂y} —————- (2)\)
\(Γ_{xy}=\frac{∂v}{∂x}+\frac{∂u}{∂y} ———(3)\)
Differentiating (1) twice with respect to y, (2) twice with respect to x and (3) once with respect to x and then y,
\(\frac{∂^2 ε_x}{∂y^2} =\frac{∂^3 u}{dx∂y^2} ————-(4)\)
\(\frac{∂^2 ε_y}{∂x^2} =\frac{∂^3 v}{dy∂x^2} ————-(5)\)
\(\frac{∂^2 Γ_{xy}}{∂x∂y}=\frac{∂^3 u}{dx∂y^2}+\frac{∂^3 v}{dy∂x^2} ——-(6)\)
∴ from (4), (5) and (6), we get,
\(\frac{∂^2 ε_x}{∂y^2} +\frac{∂^2 ε_y}{∂x^2} =\frac{∂^2 Γ_{xy}}{∂x∂y}\) which is a compatibility equation.